PROPOSED MARKETING STRATEGY FOR INCREASING SALES OF PT. PANCI BERSAMA - Puspita Sari, Dyah
In the first quarter of 2020, Indonesia's economic conditions reflect a 4.54% increase in household consumption spending over the previous year. This situation is caused by rising public demand for daily domestic appliances. Because of this tendency, home appliance firms are now facing rivalry, which has resulted in a focus on increasing product quality and expanding market share. PT. PANCI BERSAMA, a company founded in 1999, operates in the field of direct sales of household appliances with its distribution center located in Bogor City, West Java. During its 23 years of operation, the company has effectively marketed various products throughout Indonesia, including Wok Pan Streamers, Gas Stoves, Stock Pots, Pot Sets, Choppers, Pressure Cookers, and Blenders. People who live in rural areas and subareas, referred to as tier 3 and tier 4, are the company's key market categories. The company uses a push market system to market its products, which is a strategy that integrates product production with its marketing approach, focusing on cost-effective production to facilitate product promotion at prices below market prices to attract a wider consumer base. PT. PANCI BERSAMA is currently encountering challenges that represent the maturity stage in a company's product life cycle. Market saturation and declining company revenues as a result of customers' unwillingness to make more purchases have resulted in fluctuating current sales and decreasing profits. According to prior studies, customers who use credit tend to extend the life of durable items, minimizing their need for frequent replacements. Apart from that, a preliminary survey of previous buyers was completed. According to the survey results, only 30 percent of customers bought things from the company more than once, while the majority only bought things once. Furthermore, due to a variety of causes, including spending limitations and changing customer needs, 50% of respondents reported that they weren't planning to repurchase products from the company.